Cognition, loneliness and social isolation: A cross-national, longitudinal exploration. (30th September 2020) - Hannemann, T-V; Bristle, J; Wagner, M
Abstract: Background: One of the challenges to ageing individuals and health care systems is the decline in cognitive function with increasing age. The present study investigates in which way loneliness and social isolation is associated with cognitive decline in an aged population in Europe. Furthermore, it investigates how these relationships vary across different cultural and social settings. Methods: The study employs panel data from the Survey of Health, Ageing and Retirement in Europe (SHARE). Data from respondents aged 50+ from 16 European countries were collected from 2011-2017 at up to four points in time. Loneliness was operationalized as the perception of feeling lonely, while social isolation was operationalized by a summary index of social network size and social interaction. The cognitive function measures included tests of verbal fluency, as well as immediate and delayed recall. A linear panel fixed-effects modelling approach was used, while controlling for potential time-variant confounders from the areas of demographics, mental and physical health and survey methodological characteristics. Results: Preliminary results show that loneliness and social isolation are associated with cognitive decline, while the extent varied by the measure of cognitive functioning measured. Loneliness, social isolation and cognition descriptively all show substantial cross-national variation. Conclusions: The study illustrates the impact of loneliness and social isolation on cognitive functioning across a number of European countries. Cognitive functioning is an important determinant to successful ageing, preventing its decline promotes self-sufficient, independent living in the elderly and good quality end-of-life. This can support the development of implementable and accessible prevention for at risk individuals. Key messages: Investigating the impact of social isolation and loneliness on the cognitive functioning can help tailor easily accessible prevention measures of cognitive decline in the elderly. The study allows for the assessment of cross-cultural differences and need for targeted measures across a number of European countries.